1997
DOI: 10.1023/a:1005758313700
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Spinal cord astrocytomas are rare neoplasms, and optimal treatment guidelines are undefined, 23 patients with spinal cord astrocytomas were treated between 1984 and 1993 with conservative surgery and postoperative radiotherapy. The mean age was 31 years. Twelve patients were male and eleven female. All patients presented with neurologic deficit. Cervical cord was involved in five patients, cervicothoracic in four, thoracic in eight and thoracolumbar in six. Five patients had intramedullary cysts. Fifteen patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 19 publications
0
25
1
Order By: Relevance
“…Results of a statistical analysis of age as a prognostic factor were reported in 15 studies [2,5,24,27,28,30,34,41,46,49,56,59,60,64,65] (Table 4). Of these, 13 were classified as category A, 8 failed to find a significant relationship between age and prognosis [2,24,28,30,34,46,56,59], as did one additional category B study [27].…”
Section: Agementioning
confidence: 99%
See 4 more Smart Citations
“…Results of a statistical analysis of age as a prognostic factor were reported in 15 studies [2,5,24,27,28,30,34,41,46,49,56,59,60,64,65] (Table 4). Of these, 13 were classified as category A, 8 failed to find a significant relationship between age and prognosis [2,24,28,30,34,46,56,59], as did one additional category B study [27].…”
Section: Agementioning
confidence: 99%
“…Of these, 13 were classified as category A, 8 failed to find a significant relationship between age and prognosis [2,24,28,30,34,46,56,59], as did one additional category B study [27]. Four category A studies reported increased age to negatively affect prognosis: Sandler et al [64] found patients with tumor recurrence to be older (mean 38 years, median 31 years) than those without recurrence (mean 19 years, median 17 years), furthermore the oldest three patients in his study all experienced recurrence within 1 year.…”
Section: Agementioning
confidence: 99%
See 3 more Smart Citations